Success Secret of Top Management Japanese Employees in PT. Toyota Motor Manufacturing Indonesia by Using Ethnography Theory - Setiawan, Budi; Heikal, Jerry (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The Toyota Company is a large company that is spread throughout the world. With the number of employees currently reaching 370 thousand people, Toyota strives to ensure that all employees can work according to the rules and can benefit the company's progress. So Toyota's top management opens up opportunities for expatriates or Japanese Toyota employees with achievements to occupy important positions in several Toyota affiliate organizations. This research is a qualitative research using Ethnography Method. Data collection was carried out by In-depth interviews, life-histories, and documentary data. From the results of this study, it can be concluded that there are 3 of secret of success of Japanese Employee such us 1. Discipline a part of your daily life (Shitsuke), 2. Understand and Applying the TOYOTA WAY, 3. Contribute to making improvements in current operations.